2005
DOI: 10.2139/ssrn.648706
|View full text |Cite
|
Sign up to set email alerts
|

The Contracting Benefits of Accounting Conservatism to Lenders and Borrowers

Abstract: In this paper, I examine the ex post and ex ante benefits of conservatism to lenders and borrowers in the debt contracting process. First, I argue that conservatism benefits lenders ex post through a timely signal of default risk in the form of accelerated covenant violations by more conservative borrowers. I present evidence that the likelihood of a covenant violation following a negative shock increases in borrower conservatism. Second, I argue that conservatism benefits borrowers ex ante through lower initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
348
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(386 citation statements)
references
References 16 publications
31
348
3
4
Order By: Relevance
“…In both panels, the sums of coefficients on CON and CON 9 DISSUE are negative and significant in four out of the six specifications, which indicates that debt issuers also benefit from lower cost of capital with increasing conservatism. These results are consistent with prior studies that document the mitigating effects of conservatism on costs of capital (Garcia Lara et al 2011;Zhang 2008).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…In both panels, the sums of coefficients on CON and CON 9 DISSUE are negative and significant in four out of the six specifications, which indicates that debt issuers also benefit from lower cost of capital with increasing conservatism. These results are consistent with prior studies that document the mitigating effects of conservatism on costs of capital (Garcia Lara et al 2011;Zhang 2008).…”
supporting
confidence: 92%
“…Prior studies (Garcia Lara et al 2011;Zhang 2008) provide evidence that conservatism benefits firms because it is associated with lower costs of equity and debt, whereas our finding indicates that higher levels of conservatism are associated with greater likelihood of equity (versus debt) issuances. To further explore our finding, we examine changes in the costs of equity and debt surrounding issuances of debt and equity.…”
Section: Conservatism and Costs Of Equity And Debtcontrasting
confidence: 69%
See 1 more Smart Citation
“…Presumably, this preference stems from the assumption that extant accounting rules are conservative, and thereby provides a contingent upper bound to corporate payouts (Leuz 1998). Accordingly, it is often suggested that conservatism protects debtholders against expropriation by shareholders by constraining corporate payouts (Ball et al 2000;Watts 2003;Zhang 2008). We refer to this effect as the mechanical link between conservatism and dividends.…”
Section: The Potential Effects Of Conservatism On Payoutsmentioning
confidence: 99%
“…Debtholders and shareholders can foresee managers' opportunistic behaviour and demand conservatism to protect their wealth. If firms do not implement conservatism, both debtholders and shareholders will require high capital costs (Zhang 2008;Kim et al 2013). Auditors also have incentives to require managers to implement conservatism, namely, litigation and reputation risk.…”
Section: Managers' Role In Accounting Conservatismmentioning
confidence: 99%